Implementasi Steganografi Audio dan Gambar untuk Pengamanan Informasi - Faizah Amirah Harahap; Nadiyah Haaniyah Hasibuan; Luthan Asthalariq; Soty Sohaimi; Dhimas Hadi Valzoe (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of information technology has increased the risk of cyberattacks on sensitive data, creating a strong demand for advanced security techniques. Steganography complements cryptography by concealing messages within digital media so that their existence is not easily detected by unauthorized parties. This study focuses on hiding text messages in audio and image files to support secure information exchange. The research aims to implement audio and image steganography using the Least Significant Bit (LSB) method. Text messages are embedded into WAV audio files and PNG image files while maintaining media quality, minimizing detectability, and preserving file size efficiency. An experimental prototyping methodology was applied, involving system design, implementation, and testing. The LSB technique embeds messages by modifying the least significant bits of audio samples or image pixels. Data were obtained through literature review and experimental embedding and extraction procedures. The results show that text messages were successfully embedded and extracted from both audio and image files without noticeable visual or auditory degradation. File sizes remained largely unchanged, and the stego media was indistinguishable from the original as long as no compression or manipulation occurred. In conclusion, LSB-based steganography is an effective approach for information security and future enhancement research.